Differential game of pursuit time satisfy the geometric constraints in l2 space - Waziri, Usman; Ibragimov, Gafurjan; Usman, Abdullahi; Babura, Babangida Ibrahim; Adebayo, Salaudeed A. (IOP Publishing, 2021)
In the present article, we present a differential game of pursuit problem with the case of geometric constraint in the Hilbert space l2. The game is given by system of 2-infinite systems of first order ordinary differential equations (ODEs). Geometric constraint are imposed on the control functions of players. The game is began from a given point z0 called the initial position. It is given another point z1 in the space l2. The Pursuer targeting to bring the state of the system from z0 to z1 where an equation to find a guaranteed pursuit time is obtained while that of the Evader action is opposite. The game is assumed to be completed if z(t) = z1 at some time t. Moreover, a control problem is studied and then extended to the differential game of pursuit where the strategy for the Pursuer is constructed explicitly.